Pelestarian Budaya Lokal melalui Pengembangan Modul Aksara Jawa untuk Masyarakat Pesantren - Jannah, Revi Rusdatul; Jamaludin, Muhamad; Winarsih, Putri (Jurnal Pendidikan Madrasah, 2024)
This study aims to explore the development strategy of Javanese script learning modules in Islamic boarding schools as part of efforts to preserve local culture. This study uses a qualitative research method with a case study approach used to document this practice in certain Islamic boarding schools. Data were collected through in-depth interviews, participatory observations, and documentation. The results of the study show that the development of the learning module uses three methods: carangapaka tajama (learning fast and sharp scripts), the lanyahan method (the habit of reading Javanese and Pegon script fibers such as tahsin Al-Quran), and the tegesan stage (understanding the content of the manuscript). The carangapaka tajama method is effective in increasing the speed and accuracy of students' reading, the chanyahan method builds a reading habit in a sustainable manner, while tegesan allows students to understand and reflect on the content of fibers, enriching literacy skills and cultural appreciation. These findings highlight the importance of a combination of technical teaching and comprehension discussions in creating a generation that is skilled in reading and understanding the Javanese script. The strategic implications include strengthening the curriculum with integrative methods and the involvement of literary experts to increase the effectiveness of learning. This research contributes to the development of relevant learning models and supports cultural preservation in the Islamic educational environment.